Anti-Inflammatory therapeutic potential of Bungur (Lagerstroemia speciosa L.) leaves ethanolic extract against LPS-activated macrophage through TLR4/MD2 signaling: A computational study - Rosyadah Nuraini; Dwijayanti Dinia Rizqi; Annisa Yuslinda; Kamila Fairuz Sarah; Widyananda Muhammad Hermawan; Ulfa Siti Mariyah; Widodo Nashi (BIO Web of Conferences)
Excessive inflammation, driven by macrophage activation and nitric oxide (NO) production, underlies various diseases. This study investigates the anti-inflammatory potential of bungur (Lagerstroemia speciosa L.) leaf extract. We characterized its phytochemical profile and evaluated the effects using in silico approaches. Bungur leaves (L. speciosa L.) were extracted using MAE extraction and subjected to phenol, flavonoid, terpenoid, alkaloid content and antioxidant DPPH assay. The compound profile was analyzed using LC-HRMS. Identified compounds were screened in silico for drug-likeness, bioactivity, and membrane permeability. Molecular docking and molecular dynamics simulations were conducted to evaluate the interaction and stability of selected compounds with TLR4/MD2 complex. This study demonstrated that bungur leaf extract exhibited higher levels of phenolic and flavonoid compounds than terpenoids and alkaloids. This finding was confirmed by the LC-HRMS analysis, which revealed a dominance of phenolic and flavonoid compounds in the extract. The extract also showed excellent DPPH antioxidant activity, as evidenced by its low IC50 value. In silico studies identified luteolin, luteolin 7-sulfate, and quercetin as the three best compounds, which acted as potent competitive inhibitors of TLR4 activation. Therefore, compounds contained in bungur leaf exhibited promising anti-inflammatory activity through TLR4 inhibition.